C1 Inhibitor Administration Reduces Local Inflammation and Capillary Leakage, Without Affecting Long-term Wound Healing Parameters, in a Pig Burn Wound Model - Korkmaz, Halil I.; Ulrich, Magda M.W.; Wieringen, Wessel N. Van; Doğan, Hatice; Vlig, Marcel; Emmens, Reindert W.; Meyer, Klaas W.; Sinnige, Paul; Zeerleder, Sacha; Wouters, Diana; Ham, Marieke S. Van; Zuijlen, Paul P.M. Van; et al. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2021)
Background: Burns induce a boost in local and systemic complement levels as well as immune cell infiltration in the burn wound, which may negatively affect wound healing. Objective: In this study, the effects of long-term treatment with complement inhibitor C1 esterase inhibitor (C1inh) on post-burn inflammation and wound healing parameters were analyzed in time up to 60 days post-burn. Methods: Burned pigs were treated either with or without C1inh up to 15 days post-burn. Burn wound biopsies and blood were collected at different time points up to 60 days post-burn. Thereafter, complement in blood as well as complement and immune cells in the wound, capillary leakage, necrosis, reepithelialization and wound contraction were quantified. Results: No significant differences in complement C3 blood levels were observed at any time point between C1inh-treated and control pigs. In the wound, complement C4 levels were significantly lower in the C1inh group than in controls at day 3-6 and 21-30 post-burn. Similarly, C3 levels, neutrophil and macrophage infiltration in the wound were, although not statistically significant, reduced in C1inh-treated pigs at day 9-14 post-burn. No differences in lymphocyte infiltration in the wound were found between C1inh and control pigs. C1inh-treated pigs also showed reduced capillary leakage. Despite these effects, no significant differences in the long-term wound healing parameters necrosis, reepithelialization and wound contraction were observed between C1inh and control pigs. Conclusion: In pigs, 15 days of C1inh treatment after burn, leads to a reduction in local inflammation and capillary leakage in the burn wound without affecting long-term wound healing parameters.
Keywords: pig burn wound model